Comparison Method to Estimate Surface Directional Thermal Conductivity of Ultrathin Graphite Thermal Sheets - Cho, Ju Yong; Jang, Won Kweon (Asian Journal of Chemistry, 2017)
The steady state comparison method providing a simple and fast estimation for the thermal conductivity of ultrathin thermal sheet is suggested. The surface directional thermal conductivity of ultrathin graphite sheet was estimated by the steady state comparison method. The estimation was performed as a function of temperature profile along the heat spreading surface direction. At steady state condition, the temperature difference ratio of copper and aluminum ultrathin thermal sheets at the same distance from heat source showed the same value of inverse ratio of thermal conductivities of those two materials. We could find the surface directional thermal conductivity of ultrathin graphite sheet by the comparison method at the steady state. The estimated value of the surface directional thermal conductivity of ultrathin graphite thermal sheet was very close to the pre-reported value of it.